2012
DOI: 10.1016/j.actbio.2012.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and characterization of poloxamine-based hydrogels as tissue sealants

Abstract: In-situ crosslinkable polyethylene glycol (PEG)-based polymers play an increasing role in surgical practice as sealants that provide a barrier to fluid/gas leakage and adhesion formation. This study investigated the gelation behavior and physical properties of hydrogels formed from homogeneous and blended solutions of two acrylated poloxamines (Tetronics® T1107 and T904) of varying molecular weight and hydrophilic/lipophilic balance relative to a PEG control. Hydrogels were formed by reverse thermal gelation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 60 publications
5
55
2
Order By: Relevance
“…[3134] A number of studies have previously reported chemically cross-linked Tetronic ® gels prepared by polymerization of terminal reactive functional groups. [31,3644] …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3134] A number of studies have previously reported chemically cross-linked Tetronic ® gels prepared by polymerization of terminal reactive functional groups. [31,3644] …”
Section: Discussionmentioning
confidence: 99%
“…[3135] Block copolymers of PPO and PEO, including commercially available multi-arm block copolymers composed of central PPO blocks and peripheral PEO blocks (Tetronic ® ), exhibit interesting thermosensitive behavior due to the hydrophilic-to-hydrophobic transition of the PPO block that occurs by mild warming. [3134] Previous reports of chemically cross-linked Tetronic ® hydrogels for cell encapsulation and tissue adhesion have appeared in the literature, [31,3644] though systematic studies of the relationship between chemical cross-linking, thermal transition, and mechanical properties in the context of medical adhesion have not been undertaken.…”
Section: Introductionmentioning
confidence: 99%
“…The percent acrylation efficiency was calculated based on the ratio of the integrals of the PEG backbone (δ=3.5–3.7) and acrylic peaks (δ=6.15–6.4) (Figure 2) as previously shown in studies done by Cho et al (27) A yield of 22.5 g of T1107A was obtained from the original 30g of T1107 used in the synthesis and T1107A having more than 85% acrylation efficiency was used in the experiments. Efficient removal of unreacted acryloyl chloride was confirmed by the ratio of acrylate to activated PEG terminal (δ=4.3) methylene peaks, which closely approximated the theoretical value, 3:2.…”
Section: Resultsmentioning
confidence: 99%
“…(25) Briefly, T1107 (30g; 2 nmol) was dehydrated by azeotropic distillation for 2 h with toluene, which was then removed by rotary evaporation (Buchi Rotavapor®, Switzerland). After being cooled to room temperature, the dried T1107 was dissolved in 270 ml dehydrated dichloromethane and mixed with TEA (1.694 ml; 8 mmol).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation